Penghematan Air di Hotel X Kota Batam Provinsi Kepulauan Riau dengan Menerapkan Daur Ulang Air Limbah - Rio Andi Suhandi; Eka Wardhani (Fakultas Teknik, 2021)
Hotel X is a hotel located in the city of Batam, the province of the Riau Islands, which is expected to be visited by tourists on holiday in the city of Batam. As the main means of providing comfort and health to guests, Hotel X should plan a good clean water supply system in terms of quality, quantity, and continuity. Currently available clean water sources are limited, such that sufficient efforts must be made to recycle clean water. This research aims to plan water savings at Hotel X using the Green Building concept in the aspect of water conservation. The concept of this research is to recycling greywater into a second quality water source that can be used for rinsing and sprinkling water. Calculating of water requirements, generation of grey water wastewater refers to the Regulation of the 2017 Minister of Public Works and Public Housing Regulation, No. 4, Domestic Wastewater Management System. The greywater recycling process is conducted using biological and chemical processes. Based on the research use of recycled water research has the potential to conserve water use amounted to 200.32 m3/ day of total water use of 313 m3/ day or the percentage of water savings of 64%.